Are you Ernest Shackleton, the polar explorer? Refining the criteria for delirium and brain dysfunction in sepsis - Rasulo, Frank Anthony (J Intensive Care, 2017)
The Third International Consensus Definitions for Sepsis and Septic Shock has recently defined sepsis as a life-threatening organ dysfunction caused by a dysregulated host response to infection. Organ dysfunctions in this consensus definition were identified as an organ-specific Sequential [Sepsis-related] Organ Failure Assessment (SOFA) score ≥ 2 points. The quick SOFA (qSOFA) considers altered mentation indicating brain dysfunction when the Glasgow Coma Scale (GCS) score is ≤13 or ≤14. However, concern has been expressed that the revised criteria may lead to a failure in recognizing the signs of potentially lethal organ dysfunction and thus sepsis. Patients with delirium have a fluctuating course, and GCS can be normal or only slightly reduced at the time when signs of delirium are already present. We here report an illustrative case showing how an acute, initially unrecognized, urinary tract infection caused acute brain dysfunction with profound behavioral and cognitive dysfunction despite normal GCS, hence not meeting the criteria for sepsis.